2007
DOI: 10.1038/sj.npp.1301478
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences in Amphetamine Self-Administration: The Role of the Central Nucleus of the Amygdala

Abstract: Rats categorized as high responder (HR), based on their activity in an inescapable novel environment, self-administer more amphetamine than low responder (LR) rats. The current study examined if the central nucleus of the amygdala (ACe) contributes to the elevated response for amphetamine in HR rats. Male Sprague-Dawley rats were classified as HR and LR rats based on their activity in inescapable novelty and novelty place preference, and then were trained to self-administer amphetamine (0.1 mg/kg/infusion). On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 72 publications
1
34
0
1
Order By: Relevance
“…The test is relatively brief, lasting 60 min or less, and rats are categorized as HR or LR based on a median split analysis. Since the initial report by Piazza et al (1989), several studies have confirmed that HR rats show increased amphetamine-induced activity (Bevins et al, 1997) and amphetamine self-administration (Piazza et al, 1990(Piazza et al, , 2000Pierre and Vezina, 1997;Klebaur et al, 2001a;Cain et al, 2005Cain et al, , 2006Cain et al, , 2008 compared with LR rats. The differences between HR and LR rats in amphetamine self-administration are similar for both males and females (Klebaur et al, 2001a), and these individual differences generalize to other stimulant drugs, including cocaine (Mantsch et al, 2001;Sell et al, 2005;Kabbaj, 2006;Belin et al, 2008Belin et al, , 2011Walker et al, 2009) and methamphetamine (Bevins and Peterson, 2004;Gancarz et al, 2011).…”
Section: Preclinical Behavioral Neuropharmacologymentioning
confidence: 96%
See 1 more Smart Citation
“…The test is relatively brief, lasting 60 min or less, and rats are categorized as HR or LR based on a median split analysis. Since the initial report by Piazza et al (1989), several studies have confirmed that HR rats show increased amphetamine-induced activity (Bevins et al, 1997) and amphetamine self-administration (Piazza et al, 1990(Piazza et al, , 2000Pierre and Vezina, 1997;Klebaur et al, 2001a;Cain et al, 2005Cain et al, , 2006Cain et al, , 2008 compared with LR rats. The differences between HR and LR rats in amphetamine self-administration are similar for both males and females (Klebaur et al, 2001a), and these individual differences generalize to other stimulant drugs, including cocaine (Mantsch et al, 2001;Sell et al, 2005;Kabbaj, 2006;Belin et al, 2008Belin et al, , 2011Walker et al, 2009) and methamphetamine (Bevins and Peterson, 2004;Gancarz et al, 2011).…”
Section: Preclinical Behavioral Neuropharmacologymentioning
confidence: 96%
“…For example, adrenalectomy reduces HR/LR differences in morphine-induced hyperactivity . With regard to the hippocampal-prefrontal-amygdala circuitry, inactivation of the central nucleus of the amygdala with the GABA A agonist muscimol also reduces the individual differences in amphetamine self-administration and locomotor sensitization (Cain et al, 2008. Whereas direct blockade of hippocampal or prefrontal activity has not been examined directly in HR and LR rats, affinity of hippocampal type I and II corticosteroid receptors is decreased in HR rats (Maccari et al, 1991), likely because of a compensatory response to excessive levels of corticosterone.…”
Section: Preclinical Behavioral Neuropharmacologymentioning
confidence: 99%
“…The amphetamine self-administration paradigm used in this study has been employed previously to investigate individual differences in increased responding to psychostimulants (Cain et al, 2008) and its association with increased addiction risk. Therefore, the results from this study are in agreement with previous animal and clinical studies demonstrating that PSE leads to increased addiction risk and associated behavioral phenotypes (Charmandari et al, 2003;Deminiere et al, 1992;Kippin et al, 2008;Moffett et al, 2007;Thomas et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Esta mayor susceptibilidad individual en la adquisición de la autoadministración operante de anfetamina de los animales HR se replicó en otros estudios posteriores del mismo equipo (Piazza, Deminière, Maccari, Mormède, Le Moal y Simon, 1990, Piazza, Maccari, Deminière, Le Moal, Mormède y Simon, 1991 y se generalizó para la cocaína (Piazza, Deroche-Gamonent, Rougé-Pont y Le Moal, 2000). Otros laboratorios han replicado también estos datos con drogas como la anfetamina (Cain, Denehy y Bardo, 2007; Pierre y Vezina, 1997), la cocaína (Grimm y See, 1997;Mantsch, Ho, Schlussman y Kreek, 2001;Marinelli y White, 2000), la nicotina (Suto, Austin y Vezina, 2001) o el etanol (Nadal, Armario y Janak, 2002). Es interesante destacar que el estrés (derrota social) tiene efectos diferenciales en la adquisición de la conducta de autoadministración de cocaína en ambos tipos de poblaciones, de forma que la disminuye en los HR y la aumenta en los LR (Kabbaj, Norton, Kollack-Walker, Watson, Robinson y Akil, 2001).…”
Section: Búsqueda De Sensaciones Y Su Relación Con La Respuesta a Lasunclassified